The relationship between selected social factors and adolescent pregnancy in Iloilo City - Bautista, Jose Raymund Iturralde .; Funclara, Melinda Tordesillas (2004.)
This study attempts to ascertain if there is a relationship between selected social factors and adolescent pregnancy. Specifically, it aims to find out if school engagement, parental supervision, foster and kinship care, religiosity, contraceptive knowledge, mass media exposure is related to adolescent pregnancy. The researcher hypothesized that there is a relationship between these selected factors and adolescent pregnancy. Adolescent mothers between 14 to 21 years old and were either pregnant or have given birth before December 2003 from three barangays in Iloilo City were interviewed. The gathered data were subjected to Yates corrected chi-square test of independence to find out if there is any relationship between the dependent and independent variables., It was found out that school engagement, parental supervision, level of religiosity, exposure to mass media and knowledge in contraceptive use have no relationship with adolescent pregnancy. On the other hand, foster and kinship care was found to have a relationship with adolescent pregnancy. For future research directions, the researchers recommended to those who are interested in adolescent pregnancy to explore the interrelationship between the factors that contribute to adolescent pregnancy. The researchers further suggest that other factors such as economic status be explored. Increasing the number of respondents might also be helpful. Finally, the possibility that staying away from compromising situations with an opposite sex is an effective factor to prevent adolescent pregnancy could be an interesting topic.
Thesis (Undergraduate, Bachelor of Arts in Sociology-Community Development) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Adolescent pregnancy -- Iloilo City